Endoscopic transorbital resection of the temporal lobe: anatomic qualitative and quantitative study - De Rosa, Andrea; Mosteiro, Alejandra; Guizzardi, Giulia; Roldán, Pedro; Torales, Jorge; Matas Fassi, Jessica; Cavallo, Luigi Maria; Solari, Domenico; Prats-Galino, Alberto; Di Somma, Alberto; Enseñat, Joaquim (Frontiers in Neuroanatomy, 2023)
Objective Starting from an anatomic study describing the possibility of reaching the temporal region through an endoscopic transorbital approach, many clinical reports have now demonstrated the applicability of this strategy when dealing with intra-axial lesions. The study aimed to provide both a qualitative anatomic description of the temporal region, as seen through a transorbital perspective, and a quantitative analysis of the amount of temporal lobe resection achievable via this route. Material and methods A total of four cadaveric heads (eight sides) were dissected at the Laboratory of Surgical Neuroanatomy (LSNA) of the University of Barcelona, Spain. A stepwise description of the resection of the temporal lobe through a transorbital perspective is provided. Qualitative anatomical descriptions and quantitative analysis of the amount of the resection were evaluated by means of pre- and post-dissection CT and MRI scans, and three-dimensional reconstructions were made by means of BrainLab®Software. Results The transorbital route gives easy access to the temporal region, without the need for extensive bone removal. The resection of the temporal lobe proceeded in a subpial fashion, mimicking what happens in a surgical scenario. According to our quantitative analysis, the mean volume removed was 51.26%, with the most superior and lateral portion of the temporal lobe being the most difficult to reach. Conclusion This anatomic study provides qualitative and quantitative details about the resection of the temporal lobe via an endoscopic transorbital approach. Our results showed that the resection of more than half of the temporal lobe is possible through this surgical corridor. While the anterior, inferior, and mesial portions of the temporal lobe were easily accessible, the most superior and lateral segment was more difficult to reach and resect. Our study serves as an integration to the current anatomic knowledge and clinical practice knowledge highlighting and also as a starting point for further anatomic studies addressing more selected segments of the temporal lobe, i.e., the mesial temporal region.